Improving the Efficiency of Information Flow Routing in Wireless Self-Organizing Networks Based on Natural Computing - Krzysztof Przystupa; Julia Pyrih; Mykola Beshley; Mykhailo Klymash; Andriy Branytskyy; Halyna Beshley; Daniel Pieniak; Konrad Gauda (Energies, 2021)
With the constant growth of requirements to the quality of infocommunication services, special attention is paid to the management of information transfer in wireless self-organizing networks. The clustering algorithm based on the Motley signal propagation model has been improved, resulting in cluster formation based on the criterion of shortest distance and maximum signal power value. It is shown that the use of the improved clustering algorithm compared to its classical version is more efficient for the route search process. Ant and simulated annealing algorithms are presented to perform route search in a wireless sensor network based on the value of the quality of service parameter. A comprehensive routing method based on finding the global extremum of an ordered random search with node addition/removal is proposed by using the presented ant and simulated annealing algorithms. It is shown that the integration of the proposed clustering and routing solutions can reduce the route search duration up to two times.